Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray untuk Meningkatkan Prestasi Belajar Matematika Peserta Didik - Fitri Ayu Ningtiyas (Universitas Nusa Cendana, 2022)
This research is a Classroom Action Research (CAR) with the aim for improving the learning process and increasing students' mathematics learning achievement using the Two Stay Two Stray’s approach. In this study there were 20 subjects. The research was conducted in 2 cycles where each cycle consisted of 4 stages, namely planning, implementation, observation and reflection. Observations of students and learning achievement tests were carried out in collecting data in this study. If there is an improvement and the activities of teachers and students in each meeting and the number of students who reach the Minimum Mastery Criteria (MMC) increases in each cycle, the action is declared successful. In this study, it is known that on the observation sheet it is known that the activities of teachers and students have improved at each meeting. The percentage of students who succeeded in achieving the MMC on the basic score was 20% and increased in the first cycle to 40% and continued to increase to 75% in the second cycle. The results of the study provide an illustration that the cooperative learning with TSTS approach can encourage the improvement of the learning process and increase mathematics learning’s achievement of students class XII IPA 2 SMAN 11 Pekanbaru in the odd semester of the 2021/2022 academic year.